El Métraux haitiano. La construcción de una etnología religiosa - Fernando Giobellina Brumana (Journal de la Société des Américanistes)
This paper highlights the theoretical and methodological innovations of Le vaudou haïtien, and its originality for the study of cults of African origin in the Americas. Métraux achieves several key theoretical and methodological innovations in this book: 1. the search for a kind of ritual syntax; 2. a focus on real practices instead of lettered formations of the cult; 3. an acknowledgement that voodoo is unmistakably Haitian and that its roots are European as much as African; 4. a rejection of the assumption that the Catholicism of voodoo adepts would be mere deception; 5. the identification of a narrative level where stories of the gods’ avatars are replaced by tales of their interventions in the life of humans. At the same time, it explores Alfred Métraux’s relationships with some scholars that preceded him on the matter, with researchers that studied voodoo as well, and with the intermediaries that facilitated his investigation.